Diffusion Tensor Tractography Characteristics of White Matter Tracts are Associated with Post-Stroke Depression - Deng L (Dove Medical Press, 2021)
Lijun Deng,1 Rubo Sui,1 Lei Zhang2 1Department of Neurology, First Affiliated Hospital of Jinzhou Medical University, Jinzhou, Liaoning, People’s Republic of China; 2School of Nursing, Jinzhou Medical University, Jinzhou, Liaoning, People’s Republic of ChinaCorrespondence: Rubo SuiDepartment of Neurology, The First Affiliated Hospital of Jinzhou Medical University, Jinzhou, Liaoning, People’s Republic of ChinaTel +8613204525199Email 627079227@qq.comPurpose: To analyze the changes in white matter tracts in patients with post-stroke depression (PSD), and the correlation between these changes and the depressive state.Patients and Methods: The numbers of white matter tracts and corresponding fractional anisotropy (FA) in the acute phase (the onset time < 72 hours) were examined in each subject by diffusion tensor tractography (DTT). Diffusion tensor imaging (DTT), a new development of diffusion tensor imaging (DTI), enables visualization of white matter fiber tracts, which are thought to be closely related to the occurrence of PSD, According to the scores of Hamilton Depression Scale (HAMD) recorded at the 2nd week, 1st month, 3rd month, 6th month, and 12th month, forty patients were randomly selected and were classified into PSD group (n=20), non-depression post-stroke group (N-PSD, n=20), and control normal group (NORM, n=20), respectively. Correlations between the number of bundles (lines) in the white matter tract and corresponding FA, and HAMD score were finally assessed.Results: 1) FAs of the ipsilesional crossed corticocerebellar tract, the corticospinal tract, and the anterior thalamic radiation in PSD group were significantly lower than those in N-PSD and NORM groups (P< 0.01); 2) Lines in the three areas in the PSD group were significantly lower than those in the N-PSD and NORM groups (P< 0.01); and 3) FA and lines in the three areas of PSD patients were negatively correlated to HAMD scores (correlation coefficient=− 0.586, − 0.793, − 0.626, − 0.533, − 0.642, and − 0.524, respectively, all P< 0.05).Conclusion: FA and lines of the ipsilesional crossed corticocerebellar tract, the corticospinal tract, and the anterior thalamic radiation in PSD patients are significantly correlated to the depressive state. The crossed corticocerebellar tract, the corticospinal tract and the anterior thalamic radiation are involved in the development of PSD.Keywords: post-stroke depression, white matter tracts, diffusion tensor imaging, diffusion tensor tractography